Characteristics of Roman Female Deities - Kaczor, Idaliana (Studia Ceranea, 2018)
Ancient Romans’ sacral community established a cohesive and complex religious system. Its reflection was a multi-figural pantheon of gods with a variety of sacral functions that were supposed to meet the most essential material and non-material needs of the members of this religious community. This article focuses on those needs of great importance to the whole community of Rome which were met by the female figures of the Roman pantheon.